2017
DOI: 10.1155/2017/2638908
|View full text |Cite
|
Sign up to set email alerts
|

Full Step Cycle Kinematic and Kinetic Comparison of Barefoot Walking and a Traditional Shoe Walking in Healthy Youth: Insights for Barefoot Technology

Abstract: Objective Barefoot technology shoes are becoming increasingly popular, yet modifications are still needed. The present study aims to gain valuable insights by comparing barefoot walking to neutral shoe walking in a healthy youth population. Methods 28 healthy university students (22 females and 6 males) were recruited to walk on a 10-meter walkway both barefoot and in neutral running shoes at their comfortable walking speed. Full step cycle kinematic and kinetic data were collected using an 8-camera motion cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The maximum velocity deviation of the leg was observed to be m/s, and for the hand, m/s. The initial angles of the limbs were determined via physiological studies, characterizing the angle of the hands and legs during walking [ 22 , 23 ]. Using the expressions (10) and (11), the human height was evaluated.…”
Section: Human Motionmentioning
confidence: 99%
“…The maximum velocity deviation of the leg was observed to be m/s, and for the hand, m/s. The initial angles of the limbs were determined via physiological studies, characterizing the angle of the hands and legs during walking [ 22 , 23 ]. Using the expressions (10) and (11), the human height was evaluated.…”
Section: Human Motionmentioning
confidence: 99%
“…Previous studies have found extensive differences between barefoot and shod gait in healthy populations. [30][31][32][33][34] Compared to barefoot walking, shod gait resulted in smaller knee flexion and ankle plantarflexion angles throughout stance, 33,34 larger peak internal hip extensor and flexor moments throughout stance, 30,33 larger hip and knee power absorption during late stance, 33 and larger breaking forces. 30,35 There are mixed results in the literature regarding GRFs with one study detecting reduced HST magnitude and loading rate, 34,36 while others observed increased peak vertical GRF 35 or no difference in vertical GRF 30 during shod gait.…”
Section: Discussionmentioning
confidence: 99%
“…Minute changes to moments, powers, and GRF can have an immense impact on injury and can be instrumental in lower extremity injury prevention. 33 Thus, it was theorized shod gait could have an impact on gait performance following surgical intervention for AOA, particularly on the large HST magnitude found in persons with ankle fusion. 6 Despite the extant literature's findings, the present investigation failed to detect an effect of footwear, either as a two-or three-way interaction with the surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 68 , 69 Only 2 studies have compared walking in MF versus BF. 29 , 70 One study found a significant effect on kinematic gait parameters (cadence, step length, foot progression angle, and center of pressure length) and kinetic gait parameters (vGRF) between both conditions. 29 The other study reported no significant differences in kinematic knee parameters (angles) and kinetic knee parameters (net joint moments) in any planes between MF and BF, but the investigators suggested that MF might be an optimal compromise for healthy adults, considering the gait symmetry parameters.…”
mentioning
confidence: 99%
“… 29 The other study reported no significant differences in kinematic knee parameters (angles) and kinetic knee parameters (net joint moments) in any planes between MF and BF, but the investigators suggested that MF might be an optimal compromise for healthy adults, considering the gait symmetry parameters. 70 The results of the abovementioned studies are inconclusive when comparing both conditions to determine the appropriate footwear that reduces the risk factors for knee OA.…”
mentioning
confidence: 99%